Kontribusi Digitalisasi Bisnis Dalam Menyokong Pemulihan Ekonomi Dan Mengurangi Tingkat Pengangguran Di Indonesia - Adelia Safitri; Safnah Soleha; Tri Wina Sabrina; Dini Vientiany (CV. ITTC INDONESIA, 2024)
This article investigates the important role of business digitalization in facilitating economic recovery and reducing unemployment rates. By analyzing concepts such as the digital economy, e-commerce, and their impact on unemployment rates, we explain how the integration of technology has opened up new opportunities and changed the business landscape globally. Through a literature review and case studies, we present evidence that business digitalization has become a key driver in expanding market access, increasing operational efficiency, and creating new jobs. Policy and business strategy implications are also discussed to strengthen the role of digitalization in supporting inclusive and sustainable economic growth.